The application of internal suspension technique in retroperitoneal robot-assisted laparoscopic partial nephrectomy with a new robotic system KangDuo Surgical Robot-01: Initial experience - Silu Chen; Shubo Fan; Hua Guan; Kunlin Yang; Zhihua Li; Shengwei Xiong; Xiang Wang; Zhenyu Li; Cheng Shen; Liqun Zhou; Xuesong Li (Asian Journal of Urology)
Objective: To assess the feasibility of internal suspension technique in retroperitoneal robot-assisted laparoscopic partial nephrectomy (rRAPN) with a new robotic platform called KangDuo Surgical Robot-01 (KD-SR-01) system (Suzhou KangDuo Robot Co., Ltd., Suzhou, China) and discuss its surgical technique. Methods: A 44-year-old male patient was admitted with a 2.5 cm tumor on dorsolateral upper pole of the left kidney. The R.E.N.A.L. nephrometry score of this patient was 4x. This patient underwent rRAPN with KD-SR-01. The perinephric fat between the tumor and Gerota's fascia was preserved, which was used for internal suspension traction during tumor resection. Postoperative follow-up data were collected. Results: The surgery was successfully carried out with a duration of 127 min, in which the docking time was 6 min 25 s and console time was 60 min. The warm ischemia time was 19 min 53 s, and the estimated blood loss was 0 mL. The pathological histology showed a pathological tumor stage 1a clear cell renal cell carcinoma, with a negative surgical margin. The World Health Organization/International Society of Urological Pathology (WHO/ISUP) grade of this patient was Grade 2. No recurrence was observed during the 6-month follow-up. Conclusion: Internal suspension in rRAPN is feasible and effective with use of the new robotic system KD-SR-01.